2002
DOI: 10.1093/ps/81.6.774
|View full text |Cite
|
Sign up to set email alerts
|

Broiler performance, body weight variance, feed and water intake, and carcass quality at different stocking densities

Abstract: The effects of four stocking and water nipple densities on broiler performance and carcass traits were measured in two trials. The stocking densities of 23.8, 17.9, 14.3, and 11.9 birds/m2 corresponded to 260, 195, 156, and 130 birds per pen, respectively. The water nipple densities were 5, 10, 15, and 20 birds per water nipple. Birds in Trial 1 were processed at Day 39 and those in Trial 2 were processed at Day 42. Water and feed were provided ad libitum and light was provided 23 h/ d. Water nipple density ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
136
9
20

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(203 citation statements)
references
References 7 publications
38
136
9
20
Order By: Relevance
“…When examined carcass characteristics (Table 2), stocking density did not affect the carcass yield and other carcass features as also reported by previous studies (Feddes et al 2002;Dozier et al 2006). However, ad libitum feeding program increased breast meat ratio parallel to increasing BW and reduced wings, neck and back ratios.…”
Section: Resultssupporting
confidence: 82%
“…When examined carcass characteristics (Table 2), stocking density did not affect the carcass yield and other carcass features as also reported by previous studies (Feddes et al 2002;Dozier et al 2006). However, ad libitum feeding program increased breast meat ratio parallel to increasing BW and reduced wings, neck and back ratios.…”
Section: Resultssupporting
confidence: 82%
“…Table 3 show that at plot CN, the highest yield in tonnes/ha of cassava yield was 11.8 with production cost (excluding costs of seed, land clearing, planting, fertilizing and all that are common to both methods of weeding) of 11,600 naira. Figure of merit which is defined as yield in tonnes/ha per unit total production cost (Feddes et al, 1999) evaluated for the plots and shown in Table 4. The highest figure of merit was 7.52×10 -4 tonnes/ha Naira for plot CN while plot OG had 3.51 ×10 -4 tonnes/ha Naira.…”
Section: Resultsmentioning
confidence: 99%
“…Figure of merit which is defined as yield in tonnes/ha per unit total production cost (Feddes et al, 1999) for economic analysis were evaluated for different methods of cropping to determine the best methods that gave the farmer highest income. One-way ANOVA and pair t-tests were used for the statistical analysis of the relationship between the independent and dependent variables.…”
Section: Effects Of Weeds On Cropsmentioning
confidence: 99%
“…Future studies could conduct cost-benefit analyses of higher welfare standards enabling a more complete assessment of alternative options. Dawkins et al 2003;Ellendorff et al 2002;Fanatico et al 2005;Feddes et al 2002;Ghosh et al 2012;Knierim 2013;Puron et al 1995;Reiter und Bessei 2000;Stahl et al 2002;Tuyttens et al 2008;Wolf-Reuter 2004 Bodenhaltung Das Töten von Eintagsküken ist sowohl in der konventionellen als auch in der ökologischen Haltung von Legehennen üblich, weil die Mast der männlichen Küken der Legelinien aufgrund der geringen Mastleistung unrentabel ist (Damme 2015;Rautenschlein 2016). Die Geschlechtsbestimmung im Ei, die Mast der männlichen Tiere der Legehybriden oder Zweinutzungshuhnrassen bilden drei Alternativen zur Eintagskükentötung (Bruijnis et al 2015).…”
Section: Discussionunclassified